Human pluripotent stem cell derived midbrain PITX3eGFP/w neurons: a versatile tool for pharmacological screening and neurodegenerative modeling - Watmuff, Bradley; Hartley, Brigham J.; Hunt, Cameron P. J.; Fabb, Stewart A.; Pouton, Colin W.; Haynes, John M. (Frontiers in Cellular Neuroscience, 2015)
Abstract PITX3 expression is confined to adult midbrain dopaminergic neurons. In this study we describe the generation and basic functional characteristics of midbrain dopaminergic neurons derived from a human pluripotent stem cell line expressing eGFP under the control of the PITX3 promoter. Flow cytometry shows that eGFP is evident in 15% of the neuron population at day 12 of differentiation and this level is maintained until at least day 80. From day 20-80 of differentiation intracellular chloride decreases and throughout this period around ~20% of PITX3eGFP/w neurons exhibit spontaneous Ca2+ transients (from 3.3+/-0.3 to 5.0+/-0.1 min-1, respectively). These neurons also respond to any of ATP, glutamate, acetylcholine or noradrenaline with elevations of intracellular calcium. As neuronal cultures mature more dopamine is released and single PITX3eGFP/w neurons begin to respond to more than one neurotransmitter. MPP+ and tumor necrosis factor(TNF), but not prostaglandin E2, caused death of the ~50% of PITX3eGFP/w neurons (day 80). Tracking eGFP using time lapse confocal microscopy over 24 hours demonstrated significant TNF-mediated neurite retraction over time. These PITX3eGFP/w neurons are amenable to flow cytometry, release dopamine and respond to multiple neurotransmitters with elevations of intracellular calcium, we believe that they represent a versatile system for neuropharmacological and neurotoxicological studies.